PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP NIAT KONSUMEN MEMBELI SEPEDA MOTOR HONDA VARIO TECHNO 125 CBS - Pradnyana, I Wayan Bhakta; Sukawati, Tjok Gede Raka (E-Jurnal Manajemen; Vol 5 No 9 (2016), 2016)
According to the Theory of Reasoned Action of Fishbein and Ajzen, states that a person's actions are the realization of a desire or intention of a person to act. Factors affecting the intention is the attitude in action, and subjective norms regarding the perception of a person. This study aims to determine the effect of attitudes and subjective norms on consumer intentions to buy a motorcycle Honda Vario Techno 125 CBS in PT Astra Honda Motor Denpasar. Total sample in this study as many as 92 customers. Data collected by observation, interview, documentation and study questionnaires. Data were analyzed using multiple linear regression analysis. Based on the analysis states that the attitude and subjective norm positive effect on consumer intentions to buy a motorcycle Honda Vario Techno 125 CBS .
Keywords: attitude, subjective norm, consumer intentions to buy the product